Digital Entrepreneurship as Islamic Educational Management in Pesantren: Governance, Moral Supervision, and Institutional Sustainability - Akhmadi Akhmadi (JUMPA : Jurnal Manajemen Pendidikan, 2025)
The rapid advancement of digital technology has encouraged pesantren to transform their educational management systems by integrating digital entrepreneurship into institutional development while preserving Islamic educational values. However, previous studies have predominantly examined digital entrepreneurship from economic and business perspectives, with limited attention given to its role within Islamic Educational Management. This study aims to analyze how digital entrepreneurship is managed through educational planning, governance, leadership, moral supervision, and institutional sustainability in Pesantren Mamba'ul Falah, Bondowoso, Indonesia. A qualitative case study approach was employed, involving twelve participants consisting of the kyai, administrators, teachers, and santri. Data were collected through semi-structured interviews, participant observation, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that digital entrepreneurship is strategically integrated into the pesantren's educational management rather than functioning merely as an economic initiative. Educational planning emphasizes competency development, character education, and responsible digital literacy, while participatory governance and adaptive leadership ensure that technological innovation remains aligned with the institution's educational mission and Islamic values. Furthermore, moral supervision and continuous evaluation strengthen organizational learning and contribute to long-term institutional sustainability. This study proposes that digital entrepreneurship should be understood as an integral dimension of Islamic Educational Management, where educational governance serves as the primary mechanism linking digital transformation with educational quality and institutional sustainability. The findings contribute theoretically by extending the discourse on Islamic Educational Management and provide practical guidance for pesantren leaders and policymakers in developing sustainable digital entrepreneurship programs within Islamic educational institutions.